SOCS2 inhibits the tumorigenesis of GISTs and increases the sensitivity of GISTs to imatinib by suppression of KIT activation - Liangying Zhang; Kun Xiao; Shaoting Zhang; Sien Zhao; Zimei Liu; Ming Wang; Kaiyue Qin; Yuanyuan Yu; Shujing Li; Lijun Ma; Jianmin Sun (Scientific Reports)
Abstract The suppressors of cytokine signaling 2 (SOCS2) inhibits growth hormone receptor (GHR) signaling by negative feedback in the regulation of metabolism. In this study, we found that GHR upregulates SOCS2 expression, whereas KIT mutations, the key driver mutations of gastrointestinal stromal tumors (GISTs), inhibits SOCS2 expression in GISTs. Furthermore, SOCS2 associated and inhibited the activation of KIT mutations, but not wild-type KIT, in addition to its inhibition of GHR signaling, suggesting that KIT mutations may promote their activation by downregulation of SOCS2 expression. Accordingly, SOCS2 inhibited GIST cell survival and proliferation in vitro. In KITV558A/WT mice, knockout of SOCS2 expression increased the tumorigenesis of GISTs and decreased the life span of the mice. In addition, the presence of SOCS2 increased the inhibition of KIT signaling and GIST cell survival and proliferation by imatinib in vitro, and imatinib treatment further reduced tumor growth in KITV558A/WT mice compared with that in KITV558A/WT/SOCS2-/- mice, indicating the key role of SOCS2 in the sensitivity of GISTs to the targeted therapy. Taken together, our data revealed the key role of SOCS2 in the tumorigenesis of GISTs and the sensitivity of GISTs to the targeted therapy, providing a better basis for the improved treatment strategy.